The Famished Road : Ben Okri's Imaginary Homelands. - Guignery, Vanessa (Cambridge Scholars Publishing, 2013)
Some twenty years after the publication of Ben Okri's 1991 Booker Prize winning novel, The Famished Road, this volume proposes a spiralling journey into the imaginary homelands of its main protagonist, the adventurous spirit-child Azaro. Over the years, The Famished Road has been attributed a variety of mixed and sometimes contradictory labels (postcolonial, magic realist, mythopoeic, new ageist, picaresque, epic, to name just a few). Contributors to this volume have chosen to look beyond pre ...